2015
DOI: 10.1186/s13104-015-1083-2
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii infection and associated risk factors among pregnant women in Debre Tabor, Northwest Ethiopia

Abstract: BackgroundToxoplasma gondii is an obligate intracellular protozoan organism that infects both birds and mammals. Human infections are particularly serious if they occur during pregnancy and may result in abortion or congenitally acquired disorders which primarily affect the central nervous system. This study assessed seroprevalence of Toxoplasma gondii infection and associated risk factors among pregnant women at Debre Tabor, Northwest Ethiopia.MethodsAn institution based cross-sectional study was conducted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
39
4
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 22 publications
11
39
4
2
Order By: Relevance
“…Our result was lower than those reported in Ghana (92.5%) [15] and in Ethiopia (higher than 68%) [3, 8, 16, 17]. However, lower seroprevalence of T. gondii was reported in many European countries and the United States of America [18].…”
Section: Discussioncontrasting
confidence: 86%
“…Our result was lower than those reported in Ghana (92.5%) [15] and in Ethiopia (higher than 68%) [3, 8, 16, 17]. However, lower seroprevalence of T. gondii was reported in many European countries and the United States of America [18].…”
Section: Discussioncontrasting
confidence: 86%
“…For this research, there was a significant difference in T. gondii seroprevalence among different age groups ( p < 0.01). The highest T. gondii seroprevalence was found in the age range of 41-50 years (10.60%, 228/2150; OR = 2.20, 95% CI = 1.75-2.74, p < 0.01), this is similar to that reported by others (Agmas et al 2015, Cong et al 2015b. The probability of having higher seroprevalence in the age group had long duration of exposure and weak consciousness of prevention because people in this age group did more work on farming and cleaning up their homes and pet poop compared with other age groups.…”
Section: Resultssupporting
confidence: 89%
“…However, this seroprevalence of T. gondii antibodies was higher than that reported in European, North and West American continents (9, 34). Such variations could be due to different study settings in terms of multiple climatic conditions, heterogenous study population and risk factors profile such as contact with pets, hygienic practice, and feeding habit (28, 29, 31, 35, 36). The result of those who aged 21-30 years having the highest frequency of T. gondii infection (28.9%) was similar to previous reports (28, 29, 36) with the exception of one study conducted in Burkina Faso that showed these who aged more than 30 years were the most infected age group (35).…”
Section: Discussionmentioning
confidence: 99%